Determinants of participating in training: a Canadian-based analysis. Issue 1 (14th March 2017) - Weaver, Robert; Habibov, Nazim
Abstract : Purpose: The purpose of this paper is to estimate and compare the across-time individual and contextual factors influencing the participation of Canadian residents in adult education and training during the 1990s and the early twenty-first century. This era is characterized by the social investment state (SIS), a policy paradigm adopted by various developed nations throughout the world, including Canada, during the latter part of the twentieth century. Design/methodology/approach: The authors analyzed data obtained from the 1994, 1998, and 2003 versions of the Adult Education and Training Survey, which is administered by Statistics Canada. They employed binomial logit regression so as to predict the likelihood of the respondents participating in training. Findings: Participants whose level of education was below the post-secondary level were less likely to participate in training, as were adult residents of households in which pre-school children also lived. These findings occurred across all three periods of data collection. Furthermore, urban residents exhibited an increasingly greater likelihood to participate in training across-time. Research limitations/implications: Future studies should consider the funding source for training, be it from the public or private sector, and how this may affect participation. The impact that various types of training have on employment and earning patterns in developed nations should also be further assessed. Originality/value: This study, with its use of the most recent available data to analyze across-time changes in the determinants of participating in training in Canada, has contributed to the knowledge base regarding the SIS in Canada and how it compares to its European counterparts.